2022
DOI: 10.3389/fphar.2022.859628
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus and HKL Suspension Alleviates Ulcerative Colitis in Rats by Regulating Gut Microbiota, Suppressing TLR9, and Promoting Metabolism

Abstract: Ulcerative colitis (UC) is a chronic non-specific inflammatory bowel disease with complex pathogenesis. The intestinal flora disturbance affects the homeostasis of the intestinal environment, leading to metabolic imbalance and immune abnormalities of the host, contributing to the perpetuation of intestinal inflammation. We suggest that the combination of anti-inflammatory therapy and the regulation of intestinal flora balance may help in the treatment process. Previously, we used a combination treatment consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Increasing the abundance of g_Akkermansia can decrease the DAI score, restore mucosal architecture, and inhibit the release of pro-inflammatory cytokines in mice with DSS-induced UC, suggesting that g_Akkermansia holds substantial promise as a novel probiotic [34,35]. As one of the most well-known probiotics, g_Lactobacillus protects intestinal barrier function and mucosal immunity by increasing the thickness of the colonic mucosa [36][37][38][39]. In addition, it can alleviate UC by increasing the expression of TLR4/NF-κB, IL-22, and other immune-related genes, restoring intestinal mucosal barrier function, modulating gut microbiota dysbiosis, and inhibiting the growth of pathogenic bacteria [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the abundance of g_Akkermansia can decrease the DAI score, restore mucosal architecture, and inhibit the release of pro-inflammatory cytokines in mice with DSS-induced UC, suggesting that g_Akkermansia holds substantial promise as a novel probiotic [34,35]. As one of the most well-known probiotics, g_Lactobacillus protects intestinal barrier function and mucosal immunity by increasing the thickness of the colonic mucosa [36][37][38][39]. In addition, it can alleviate UC by increasing the expression of TLR4/NF-κB, IL-22, and other immune-related genes, restoring intestinal mucosal barrier function, modulating gut microbiota dysbiosis, and inhibiting the growth of pathogenic bacteria [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion of microbes to intestinal epithelial cells (ECs) is key to inducing Th17 cells. p_Proteobacteria can adhere to the intestinal epithelium and promote the release of IFN-γ by inducing Th1 cells under the recognition of TLR9 [38,46]. This phenomenon may be one of the reasons for the imbalance of cytokines in UC.…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted metabolomics can reveal important biological associations in immunology research and identify novel metabolites/biomarkers specific to a disease (Ding et al , 2021b ; Alboniga et al , 2022 ; Aximujiang et al , 2022 ; Chen et al , 2022 ; Tian et al , 2022 ). For example, Zhu et al ( 2022 ) used high‐resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa.…”
Section: Targeted and Untargeted Metabolomics For Immunology Researchmentioning
confidence: 99%
“…This approach is currently widely used in the discovery of biomarkers, disease diagnosis, and mechanism research, and it provides new insights into the complex study of disease mechanisms (Haimerl et al, 2021;Krishnan et al, 2021;Roberts et al, 2021;Choueiry et al, 2022). Untargeted metabolomics can reveal important biological associations in immunology research and identify novel metabolites/biomarkers specific to a disease (Ding et al, 2021b;Alboniga et al, 2022;Aximujiang et al, 2022;Chen et al, 2022;Tian et al, 2022). For example, Zhu et al (2022) used high-resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa.…”
Section: Untargeted Metabolomicsmentioning
confidence: 99%
“…Lactobacillus and Bifidobacterium suppress animal enteritis by reducing TNF-α by TLR4 ( 39 ). It has been shown that the promotion of IFN-γ release via TLR9 by S. amoebae may contribute to cytokine imbalance in UC ( 40 ). Abnormal TLR signaling activation in immune cells may also lead to the release of pro-inflammatory cytokines, resulting in acute or chronic intestinal inflammation ( 41 ).Additionally, TLRs, activated by microbiota, can also start adaptive immune responses.…”
Section: Strategies For Gut Microbiota To Increase the Efficiency Of ...mentioning
confidence: 99%